1984
DOI: 10.1002/pssa.2210830109
|View full text |Cite
|
Sign up to set email alerts
|

A study of the non-stoichiometrical halogen and water content of β-FeOOH

Abstract: W l and 'SF neutron activation analysis is used to determine the halogen content of synthetic P-FeOOH. Combined with 67Fe Mossbauer spectroscopy and TGA, new data are presented concerning the nature of the anion location and its role in the structure. A stoichiometrical model is proposed, allowing to obtain a more detailed knowledge of the content of interstitial water molecules in the compound.87Cl-und l0F-Neutronenaktivierungsanalyse wird benutzt, um den Halogengehalt von synthetischem p-FeOOH zu bestimmen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 5 publications
2
15
1
Order By: Relevance
“…Analysis of akaganeite‐free pH 0 4/Cl 0.02 M, pH 0 6/Cl 0.02 M, and pH 0 8/Cl 0.02 M samples showed that little Cl − (≤0.3 wt %) was associated with Fe(III) (hydr)oxides (Figure a and Table ) in agreement with our previous observations (Peretyazhko et al, ). We, therefore, assume that chloride detected in akaganeite mixtures was associated with akaganeite tunnels, although we cannot exclude minor amount of Cl − adsorbed onto akaganeite surfaces (Chambaere & Degrave, ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of akaganeite‐free pH 0 4/Cl 0.02 M, pH 0 6/Cl 0.02 M, and pH 0 8/Cl 0.02 M samples showed that little Cl − (≤0.3 wt %) was associated with Fe(III) (hydr)oxides (Figure a and Table ) in agreement with our previous observations (Peretyazhko et al, ). We, therefore, assume that chloride detected in akaganeite mixtures was associated with akaganeite tunnels, although we cannot exclude minor amount of Cl − adsorbed onto akaganeite surfaces (Chambaere & Degrave, ).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of weight loss, XRD data and quite similar variations of Cl/Fe ratio, the endothermic minimum at 230 8C should be attributed mainly to the loss of interstitial water instead of water removal from the tunnels, as has been suggested earlier [8,10,12]. According to determined Cl/Fe ratio (Table 4), the composition of b-FeOOH,Cl should be expressed by the formula FeOOHÁ0.163HClÁxH 2 O, where xH 2 O is the content of interstitial water [28], whereas the composition of the product after annealing at 230 8C is close to FeOOHÁ0.153HCl.…”
Section: Data From the Thermal And Edx Analysesmentioning
confidence: 93%
“…One of the most commonly employed manufacturing protocols for hematite involves crystallization from precursor akaganeite [ β -FeO(OH,Cl); space group I 2/ a ; Figure 2], which has a hollandite-like structure. In akaganeite, edge-linked octahedral chains form tunnels along (010) that are supported by Cl − or similarly sized anions, such as F − or OH − (Weiser and Milligan, 1935; Mackay, 1960; Chambaere and De Grave, 1984; Post and Buchwald, 1991; Cai et al ., 2001; Cornell and Schwertmann, 2003; Post et al ., 2003a). Based on a Rietveld analysis of powder X-ray diffraction data, Post and Buchwald (1991) report that Cl fills ~2/3 of the tunnel sites.…”
Section: Introductionmentioning
confidence: 99%